Self-efficacy for learning beliefs in collaborative contexts: relations to pre-service early childhood teachers’ vicarious teaching self-efficacy - Yim, Eunice Pui-yu (Frontiers in Education, 2023)
: relations to pre-service early childhood teachers' vicarious teaching self-efficacy The importance of academic self-efficacy generally outweighs social selfefficacy in teacher training in academia. Given the teaching profession is collaborative career, social self-efficacy should play a significant role in the success of teacher training within and outside of academia. Students taking an early childhood teacher training program in a tertiary institute in Hong Kong (N=513) responded to survey items concerning three personal self-efficacy for learning variables (academic self-efficacy, social self-efficacy and control of learning) and vicarious experiences as a source of teaching self-efficacy.Academic self-efficacy, social self-efficacy and control of learning were found to be 1) related but distinctive to one another, and 2) positively related to vicarious experiences as a source of teaching self-efficacy. Practicum experience was found to have no significant impact on any of the personal self-efficacy for learning variables and the social-oriented vicarious source of teaching self-efficacy. This study suggested that as a source of teaching selfefficacy for pre-service teachers, vicarious experiences could be as important Early Childhood Teachers' Self-efficacy 2 as experiences of teaching skills mastery. Moreover, practicum that does not optimize the interplay of personal self-efficacy for learning variables with vicarious experiences as a source of teaching self-efficacy, and does not fully consider cultural sensitivities, would not contribute significantly to teachers' learning and social competence. The development of different domains of self-efficacy is not only affected by different sources of teaching self-efficacy but also varies between pre-service and experienced teachers. This study renewed the existing understanding of the reciprocal influences of personal self-efficacy for learning and vicarious experiences as a source of teaching efficacy, which can be fostered by teacher education programs. Future studies will be required to explore the culturalization of sources of teaching selfefficacy, how different components of personal self-efficacy for learning change over career stages and time, and how the transfer of learning between practicum and academia can be further enhanced.